Recurrent and Residual Aneurysms After Woven EndoBridge (WEB) Therapy: What’s Next? - Peterson, Catherine (Cureus, 2021)
The prevalence of recurrent and residual aneurysms following Woven EndoBridge (WEB) treatment is not insignificant. The goal of this systematic review was to evaluate retreatment methods for such aneurysms and their outcomes. PubMed, Embase, and Scopus databases were systematically searched, and results were reported according to the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. Original studies reporting on aneurysms that were retreated after WEB were included. Sixteen studies (n = 901 aneurysms), of which three were prospective, reported on retreated aneurysms following initial WEB treatment. Of those 901 aneurysms, on average 18.7 ± 11.5% were recurrent or residual at the last follow-up and 10.7 ± 11% required some form of retreatment. When compared to WEB-IT (WEB Intra-saccular Therapy) data, retreated aneurysms were more likely to be large in size (p < 0.0001) and more likely to have been initially treated with the WEB dual-layer configuration. The mean age of those with retreated aneurysms was 58 ± 5.7 years old, and the mean size of aneurysm dome was 11.1 ± 5.5 millimeters. Majority (34.1%) of the aneurysms were located at the basilar apex. Retreatment modalities included coiling (20%), stent-assisted coiling (38.7%), additional WEB device (13.3%), flow diversion (16%), and clipping (12%). Majority of retreated cases had favorable outcomes, with 96.4 ± 13.4% of the cases demonstrating technical success and 90.5 ± 18.2% having adequate occlusion at the last follow-up. Our systematic review suggests that retreatment of recurrent and residual aneurysms after initial WEB treatment is feasible. Future prospective studies would be helpful in validating these results.